CLINICAL PROTOCOLS IN ADVICE TO CHRONIC PATIENTS - Maria de Fátima Mantovani; Juliana Perez Arthur; Ângela Taís Mattei; Elis Martins Ulbrich; Luciana Puchalski Kalinke (Universidade Federal do Paraná, 2015)
Qualitative study, undertaken in three phases between 2012 and January 2014 to verify the use of clinical protocols when giving advice to chronic patients. The initial data collection took place upon discharge from the hospital, the second at home after 12 months and the third after 24 months. The sample consisted of 20 hypertensive and/or diabetic adults hospitalized at a teaching hospital in Curitiba, Brazil. Based on the data analysis, three categories were constituted: "Knowledge about the disease", "Care with regard to the disease" and "Barriers for treatment adherence". It was identified that the advice, through the use of clinical protocols, furthered the knowledge about the disease and the care the participants developed. In conclusion, the use of the protocols is a health education strategy for chronic patients. They make the care feasible and reveal the progress made and difficulties found.